Phonological Variation in Kui: A Dravidian Language - Pradhan, Gajindra; Kujur, Anup Kumar (International Journal of Language and Literary Studies, 2026)
Phonological variation in Kui is examined with a focus on organization of the vowel system, an area that has had relatively little research compared to other areas such as the composition of the inventory of segments or overall regional variations of pronunciation. The data analyzed were collected from field recordings at three locations (Baliguda, G. Udayagiri, and Phulbani) and a detailed record was kept of the responses to vowel forms used in various interactions by speakers. Vowels are viewed as categories recovered from repeated lexical distributions of vowels, as opposed to being viewed as categories derived from the elicitation of vowel contrasts. The results of this study indicate that the vowel system of Kui maintains structural stability with regional conditioned variation in vowel quality and duration occurring within the established phonemic categories so that speakers can maintain mutual intelligibility. There is no evidence of the merger, loss or reclassification of vowel categories. Although there are regional variations, they occur within the established phonemic boundaries. Variation involves controlled changes in quality, duration and degree of centralization; however, the categorical structure of the vowel system is maintained and does not result in disruption of the categorical structure of vowel systems shared by speakers. Prototypical realizations are identified through frequency and routine use; however, peripheral variants remain recognizable without difficulty. Observations regarding perception reveal that speakers interpret regional variation through stable relationships among vowel categories rather than through exact acoustic matches. While contact with Odia influences certain vowel realization(s) in certain contexts, it does not result in the reorganization of the vowel system. Collective evidence suggests that speakers can internally regulate their use of variation to communicate effectively with one another when using every type of Kui.